Clear Cell Carcinoma of Cervix: A Rare Case Report - Manivannan, Charanya; Sundaram, Sandhya (Annals of Pathology and Laboratory Medicine, 2019)
Clear cell carcinoma of cervix is a rare tumor, accounting for about 4% of cases of cervical adenocarcinoma. It commonly occurs in young women whose mothers had been exposed to diethylstilbestrol (DES). We are reporting a case of clear cell carcinoma of cervix in a 58 year old postmenopausal woman with no history of intrauterine exposure of DES.